2019
DOI: 10.1002/dev.21884
|View full text |Cite
|
Sign up to set email alerts
|

Isolation calls in house mouse pups: Individual consistency across time and situations

Abstract: Isolation calls are emitted by the offspring of many mammalian species when separated from caregivers and siblings. Some studies indicate that isolation call rates constitute a consistent individual trait; others show that the young adjust their vocalization rate to the current situation. We studied this in the house mouse (Mus musculus domesticus) by exploring individual consistencies in pup isolation call rates and their potential modulation in different social situations. We carried out experiments includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Exposing isolated mouse or rat pups to familiar nest scents significantly decreases vocalization rates, similar to contact quieting (Oswalt and Meier 1975;Geyer 1981;Verjat et al 2019;reviewed in Shair 2007). In contrast, exposing pups to predator odor has been found to either increase (Verjat et al 2019) or have no effect on calling rates (Wiedenmayer and Barr 1998).…”
Section: Introductionmentioning
confidence: 77%
“…Exposing isolated mouse or rat pups to familiar nest scents significantly decreases vocalization rates, similar to contact quieting (Oswalt and Meier 1975;Geyer 1981;Verjat et al 2019;reviewed in Shair 2007). In contrast, exposing pups to predator odor has been found to either increase (Verjat et al 2019) or have no effect on calling rates (Wiedenmayer and Barr 1998).…”
Section: Introductionmentioning
confidence: 77%
“…The number of audio recordings per age and per sex were as follows: control (P6 [female, n = 9; male, n = 7], P8 [female, n = 14; male, n = 9], P10 [female, n = 10; male, n = 13], and P12 [female, n = 15; male, n = 15]) and Magel2 m+/p− (P6 [female, n = 10; male, n = 10], P8 [female, n = 15; male, n = 13], P10 [female, n = 11; male, n = 9], and P12 [female, n = 16; male, n = 12)]. Because pups that were naïve for the test—only tested at one specific age—show similar results as pups tested at multiple ages (Figure S3, similar to previous findings 43,44 ), we pooled all mice together for our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Pups from the same litter were placed individually in a soundproof chamber containing fresh bedding material. 23,39 An UltraSoundGate Condenser Microphone CM 16 (Avisoft Bioacoustics, Berlin, Germany) was placed 10 cm above the recording chamber and con- S3, similar to previous findings 43,44 ), we pooled all mice together for our analysis.…”
Section: Separation-induced Vocalizationmentioning
confidence: 99%
“…Because pups that were naïve for the test-only tested at one specific age-show similar results as pups tested at multiple ages, we pooled all mice together for our analysis. Moreover, literature in the field have reported that repeated isolation testing does not affect infant vocal behavior 29,30 . Details of individual behavior measurements are found in Table S1.…”
Section: Behavior Testmentioning
confidence: 99%
“…Towards this end, we studied how the loss of paternally inherited Magel2 affects the vocal behavior of mouse pups when separated from their dams [15][16][17][18][19][20][21][22][23] , as separation-induced vocalizations signal the needs of the pups to the dams 19,[24][25][26][27][28][29] . In contrast to human babies, mouse pups vocalize in the ultrasonic frequency range (45 -120 kHz) 20,21,23,30 , which humans cannot hear. In order to survey the vocal behavior of mice, we recorded the emission of ultrasonic vocalizations (USVs) when pups were separated from the home nest.…”
Section: Introductionmentioning
confidence: 98%